2021
DOI: 10.1159/000515183
|View full text |Cite|
|
Sign up to set email alerts
|

The Usefulness of a Simple Classification for Bronchoscopic Findings for Diagnosis of Peripheral Pulmonary Tumour

Abstract: <b><i>Background:</i></b> Normal bronchial epithelium has been described in terms of transparency and smoothness. No studies have compared bronchoscopic and pathological findings in the identification of bronchial epithelium. <b><i>Objectives:</i></b> This study aimed to classify bronchoscopic findings for peripheral pulmonary tumour (PPT) for accurate bronchoscopic diagnosis accounting for the presences of bronchial epithelium and bronchial stenosis using an ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In 2021, Fukada et al proposed a simple system to classify the bronchoscopic images of peripheral pulmonary tumor (PPT) ( 129 ). Based on the appearance of stenosis, the lesions were divided into stenotic type (ST) and non-stenotic type (NonST).…”
Section: Bronchus and Lungsmentioning
confidence: 99%
“…In 2021, Fukada et al proposed a simple system to classify the bronchoscopic images of peripheral pulmonary tumor (PPT) ( 129 ). Based on the appearance of stenosis, the lesions were divided into stenotic type (ST) and non-stenotic type (NonST).…”
Section: Bronchus and Lungsmentioning
confidence: 99%
“…The bronchoscopy-pathology correlation study by Fukada and colleagues [13] reported in this issue provides an explanation as to why tissue sampling after arrival at the target lesion with confirmation by R-EBUS may not yield a diagnosis. The investigators used a physiological saline injection technique to dilate the small peripheral airways, leading the tumor to allow clearer observation of the endo-luminal features and then classified them into a stenotic or nonstenotic type and to determine if the tumor was exposed on the surface or submucosal with an intact ciliated epithelium as reflected by a light blue line using narrow band imaging.…”
mentioning
confidence: 99%
“…The findings of the study by Fukada and colleagues [13] have practical implications. The use of ultrathin bronchoscopes and injection of physiological saline to dilate the small peripheral airways leading the tumor to allow clearer observation of the endo-luminal features to position forceps or TBNA needles for tissue sampling should lead to a higher diagnostic yield of small peripheral tumors [17].…”
mentioning
confidence: 99%